Coronary Microvascular Remodeling in Type 2 Diabetes: Synonymous With Early Aging? - McCallinhart, Patricia E.; Sunyecz, Ian L.; Trask, Aaron J. (Frontiers in Physiology, 2018)
Type 2 diabetes mellitus (T2DM) is suggested to cause an “early vascular aging” phenomenon that is associated with vascular dysfunction, remodeling, and adverse alterations in vascular stiffness. Given that both T2DM and aging are prominent risk factors for cardiovascular disease, the aim of this study was to test the hypothesis that CRM remodeling and impairments in flow occur in the compound setting of T2DM and aging. Normal heterozygous Db/db controls and homozygous db/db mice were aged to 16 (young) or 36 (aged) weeks for all experiments and passive pressure myography and echocardiography were used to assess vascular mechanics, and structure. CRM wall thickness was significantly increased at each pressure in aged control mice compared to young control mice (9.4±0.6 vs. 6.8±0.2 µm, respectively, p<0.001); however, there were no significant differences in CRM wall thickness of aged db/db mice vs. young db/db mice. Aged control mice had a higher medial CSA compared to young control mice (3847±303 vs. 2715±170 µm2, p<0.01); however there were no significant differences in medial CSA of aged db/db mice vs. young db/db mice. Elastic modulus was lower in aged control CRMs vs. young control CRMs (3.5x106±0.7x106 vs. 8.7x106±0.6x106, p<0.0001). Elastic modulus remained the same in young db/db mice vs. aged db/db mice. These data show that the diabetic CRMs undergo adverse remodeling at an early age, similar to normal aged CRMs, that persists towards senescence, and it further suggests that diabetic CRMs are subject to an early aging phenomenon.